The honey bee “hive” microbiota: meta-analysis reveals a native and aerobic microbiota prevalent throughout the social resource niche - Anderson, Kirk E.; Copeland, Duan C. (Frontiers in Bee Science, 2024)
The microbiome of the honey bee worker hindgut has been explored thoroughly with culturing and next generation sequencing revealing both composition and function. However, less effort has been devoted to the aerobic social niches associated with the hive environment and colony process. We performed a meta-analysis of 3800+ publicly available 16S rRNA gene sequence libraries examining the hypothesis of a native aerobic microbiota associated with social interaction and colony resources. We selected high-throughput studies to represent tissue-specific samples, including nine distinct aerobic niches throughout the colony and hive, defined by social nutrient processing. These included queen and worker gut tissues, foregut, midgut, ileum, rectum, mouthparts, worker social glands, developing larvae and secreted and stored nutrition. We found that the aerobic mouthparts, foregut and midgut niches of queens and workers share a significant portion of their microbiome with that of larval rearing and nutrient secretion and storage, defining the microbiota of the social resource niche. Characterized by species dominance and rapid growth, the social resource microbiota functions primarily in disease prevention at both the individual and colony level, and may also function in social communication and gut microbiome resilience. Defining the microbiota of social function contributes to a systems-level understanding of host-microbial interactions in the honey bee.